A case of sporadic late‐onset nemaline myopathy without monoclonal gammopathy of unknown significance/human immunodeficiency virus successfully treated with intravenous gamma globulin. Issue 2 (5th December 2020) - Fukazawa, Ryosuke; Cho, Masanori; Hidaka, Yukihiro; Takezawa, Hidesato; Ogasawara, Masashi; Nishino, Ichizo; Fujii, Akihiro
Abstract: Background: Sporadic late‐onset nemaline myopathy (SLONM) is an acquired form of nemaline myopathy developed in adulthood. Due to its rarity, standard treatment has not been established albeit some reports suggest treatment efficacy. Case presentation: A 75‐year‐old woman developed progressive muscle weakness in her extremities 3 years previously. Muscle biopsy revealed nemaline bodies, which led to the diagnosis of SLONM. M protein, human immunodeficiency virus (HIV) antigen/antibody, and urine Bence‐Jones protein were all negative. Muscle strength gradually improved after receiving two courses of intravenous immunoglobulin (IVIg). Conclusions: IVIg may be effective in SLONM without monoclonal gammopathy of unknown significance or HIV infection by improving symptoms and suppressing the progression. Abstract : IVIg may be effective in SLONM without MGUS or HIV infection by improving symptoms and suppressing the progression.